Experiential Learning on an Urban Farm: Hands-on pedagogy for deep learning, sustainability, food security, and social justice - Carlos, Alfredo; Hall, Jenney (Experiential Learning and Teaching in Higher Education, 2024)
Join CSU Dominguez Hills faculty Alfredo Carlos (Labor Studies) and Jenney Hall (Interdisciplinary Studies) for a couple of minutes with the university’s urban farm and current students. Here the learning is literally hands-on: students leave with a firsthand understanding of the basic principles of agriculture, soil, and sustainability, while better able to address the environmental degradation and food insecurity that beset city dwellers, all without leaving home.